2023
DOI: 10.21203/rs.3.rs-2330932/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut-microbiota in Obese Children and Adolescents: Inferred Functional Analysis and Machine-learning Algorithms to Classify Microorganisms

Abstract: The fecal microbiome of 55 obese children and adolescents (BMI-SDS 3.2+/-0.7) and of 25 normal-weight subjects, matched both for age and sex (BMI-SDS -0.3+/-1.1). Streptococcus, Acidaminococcus, Sutterella, Prevotella, Sutterellawadsworthensis, Streptococcus thermophilus, and Prevotellacopri positively correlated with obesity. The inferred pathways strongly associated with obesity concern the biosynthesis pathways of tyrosine, phenylalanine, tryptophan and methionine pathways. Furthermore, polyamine biosynthes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Higher abundances of Parabacteroides merdae (SGB1949) have been found in obese mice and have also exhibited a protective effect against obesity-associated atherosclerosis. 36 In human studies, Butyrivibrio crossotus (SGB5065) was found to be enriched in non-obese individuals, 37 and Sutterella wadsworthensis (SGB9286; one of our strongest positively correlated species) was found to be 10 times more abundant in obese children-adolescents 38 —both of which were consistent with these meta-analysis findings.…”
Section: Resultssupporting
confidence: 79%
“…Higher abundances of Parabacteroides merdae (SGB1949) have been found in obese mice and have also exhibited a protective effect against obesity-associated atherosclerosis. 36 In human studies, Butyrivibrio crossotus (SGB5065) was found to be enriched in non-obese individuals, 37 and Sutterella wadsworthensis (SGB9286; one of our strongest positively correlated species) was found to be 10 times more abundant in obese children-adolescents 38 —both of which were consistent with these meta-analysis findings.…”
Section: Resultssupporting
confidence: 79%
“…Leuconostoc mesenteroides , mediating an electrogenic pathway to attenuate the accumulation of abdominal fat mass induced by HFD [35], was enriched in HFD‐fed mice in our study. Streptococcus thermophilus positively correlated with obesity [36], was enriched in HFD‐fed mice. Parabacteroides goldsteinii , represents novel prebiotics and probiotics that may be used to treat obesity and type 2 diabetes [37], was significantly enriched in HFD‐fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…in ammation [19], cardiovascular diseases [31], and diabetes [32], and to explore the potential causal relationships of microbes with these diseases. The relationship between the gut microbiome and lipid metabolism in individuals with obesity has been widely investigated using machine learning [33][34][35][36]. For example, Bacteroides caccae, Odoribacter splanchnicus and Roseburia hominis were identi ed as obesity-related biomarkers using a vector machine model (0.485 R 2 ) in 2262 Chinese individuals, and obese individuals exhibited decreased diversity of these species [34].…”
Section: Discussionmentioning
confidence: 99%